Influence of drip irrigation, crop geometry and mulching on morphological and nutritional traits of okra (Abelmoschus esculentus) - MEENA, ATMA RAM; NAROLIA, RAJEEV KUMAR; KUMAR, LOKESH; MEENA, SIYARAM (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during rainy (kharif) seasons of 2019 and 2020 at College of Agriculture, Swami Keshwanand Rajasthan Agricultural University, Bikaner, Rajasthan to study the effect of crop geometry, mulching and different irrigation levels on the morphological and nutritional traits of okra [Abelmoschus esculentus (L.) Moench]. The experiment was conducted in a split plot design (SPD) comprised of 4 irrigation levels in the main plot (40%, 60%, 80% and 100% pan evaporation) and 2 different crop geometry (paired row sowing and normal sowing) and 3 types of mulches (no mulch, plastic mulch and straw mulch) were employed in the subplots and sub-subplots, respectively. Results indicated that 100% potential evapotranspiration (PE), drip irrigation (DI) and paired row sowing at 30 cm × 70 cm significantly increased the number of branches/plant, plant height (cm), length of fruit (cm), diameter of fruit (cm) and chlorophyll content of leaves compared to lower irrigation levels and normal sowing. Additionally, straw mulch positively influenced the above-mentioned parameters in the okra fruits as compared to without mulch. Drip irrigation, paired row sowing, and straw mulching also resulted in a significant increase in net returns per hectare. The study demonstrated that combining paired row sowing with straw mulch and irrigating at 100% potential evapotranspiration (PE) yielded the best growth attributes, highest fruit quality, and maximum net returns for okra.